2021
DOI: 10.21203/rs.3.rs-480385/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensitization of the UPR by Loss of PPP1R15A Promotes Fibrosis and Senescence in IPF

Abstract: The unfolded protein response (UPR) is a direct consequence of cellular endoplasmic reticulum (ER) stress and a key disease driving mechanism in IPF. The resolution of the UPR is directed by PPP1R15A (GADD34) and leads to the restoration of normal ribosomal activity. While the role of PPP1R15A has been explored in lung epithelial cells, the role of this UPR resolving factor has yet to be explored in lung mesenchymal cells. The objective of the current study was to determine the expression and role of PPP1R15A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A previous study examining wound healing, showed that mice lacking PPP1R15a exhibited accelerated wound closure, increased number of myofibroblasts, and elevated collagen production 36 . A recent report has also shown that mice lacking Ppp1r15a show increased pulmonary fibrosis in response to the DNA damage inducing chemical bleomycin 37 . Taken together, these data suggest that the PP1R15A may play an important role in the negative regulation of fibrosis pathways.…”
Section: Discussionmentioning
confidence: 93%
“…A previous study examining wound healing, showed that mice lacking PPP1R15a exhibited accelerated wound closure, increased number of myofibroblasts, and elevated collagen production 36 . A recent report has also shown that mice lacking Ppp1r15a show increased pulmonary fibrosis in response to the DNA damage inducing chemical bleomycin 37 . Taken together, these data suggest that the PP1R15A may play an important role in the negative regulation of fibrosis pathways.…”
Section: Discussionmentioning
confidence: 93%
“…CCL4 and CCL5 are potent chemo attractants for a variety of cells, among which are NK and T cells (25,26). IKBKB is an activator of NF-κB-dependent apoptotic pathways and PPP1R15A, whose functions associate with negative regulation of TGF-b signaling (27,28).…”
Section: Ifn-γ Mediates Adaptive Resistance In Bcg-unresponsive Tumorsmentioning
confidence: 99%